Fremdsprachenlehrerausbildung in Zeiten der Coronapandemie: Microteaching im digitalen Format - Hedžić, Lara (Neofilolog, 2023)
Microteaching as a specific method in foreign language teacher education in which theoretical knowledge is put into practice, offers prospective teachers systematic, small-step and practice-oriented training of teaching behaviour and teaching skills in the form of classical microteaching (practical exercises in small groups of students), or peer teaching (training in small groups of fellow students). Due to the pandemic-related switch to digital teaching formats in university foreign language teacher training, microteaching also had to be moved from the traditional classroom to the digital space and had to face completely new challenges. The paper aims to explore the method of microteaching from a theoretical and empirical perspective and to demonstrate its possibilities and limitations in the digital format, using the example of a microteaching course with students at the Faculty of Philosophy, University of Sarajevo, Bosnia and Herzegovina. Results of a survey among future teachers of German as a foreign language on the effectiveness of microteaching in the digital format in the times of the coronavirus pandemic will be presented.